Allusive References and Other‐Oriented Stance in an Affinal Avoidance Register. (24th April 2018) - Mitchell, Alice
Abstract : This paper analyzes the social‐relational dynamics of in‐law name avoidance in Datooga, a Nilotic language spoken in Tanzania. Datooga women avoid referring to their senior affines by birth name, while also avoiding words that "allusively" refer to these in‐laws by sharing lexical or phonetic material with their names. These acts of name avoidance are conceptualized here in terms of stance: each instance of avoidance orients the speaker toward her affinal kin. The analysis of this unusual phenomenon emphasizes how speakers construct social relations in discourse not only with immediate speech participants but also with absent others, across time and space.